Development of an electronic wireless monitoring mailbox using RF module - Che Amat, Mohd Juhaidi (2013)
This thesis presents on the development of a prototype Electronic Wireless Monitoring Mailbox using Radio Frequency (RF) Module that can monitor the current status of user’s mailbox. Mailbox is an important gadget that receives letter or mail but unfortunately its existence is barely noticeable. Users normally do not notice of a received mail even though they are at home or as for the flat or condominium dwellers, since their mailbox are located away from their apartments, a received mail will normally be unnoticeable. In an attempt to solve the above problem, a concept of mailbox notification system and mail minder that uses wireless RF module is introduced. This system allows users to check remotely the status on a received mail of their mailboxes. A new way to transfer input data on the mailbox is using wireless RF module. IR sensor placed in the mailbox is used to detect an incoming mail, this act as an incoming data. The RF transmitter will transmit the incoming data received from the mailbox to the receiver. Users are able to check the status of their mailboxes via an LCD display located at their house. It is also hoped that the developed system could assist the disabled and also the old folks. The main development tools used for this project are ATMEGA 328, wireless RF module 433MHz, digital IR sensor and other components.